THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE JOB SATISFACTION - Gabrella Nuranda; Kasmari Kasmari (Jurnal Ekonomi, 2023)
The pupose of this study was to determine the effect of leadership, motivation, career development on employee's job satisfaction at PT Maha Sentral Sejati Semarang. The research method using quantitative with distributing questionnaires. The population in this research study were consisted of 102 employees at PT Maha Sentral Sejati Semarang. After using the Slovin's formula for sampling, the number of samples became 81 employees as respondents. The sampling technique used was purposive sampling method. The research instrument was carried out using a validation method with a loading factor value > 0.4, and a reliability test with Cronbach Alpha value > 0.70. The results of the research analysis was done using multiple regression by using the SPSS 23 program. The result showed that leadership had a positive and significant effect on employee's job satisfaction, motivation had a positive and significant effect on employee's job satisfaction, career development had negative and no effect significant on employee's job satisfaction.